Targeting Regulatory T Cells to Treat Patients With Systemic Lupus Erythematosus - Mizui, Masayuki; Tsokos, George C. (Frontiers in Immunology, 2018)
Regulatory T cells (Tregs) are central in integration and maintenance of immune homeostasis. Since breakdown of self-tolerance is a major culprit in the pathogenesis of systemic lupus erythematosus (SLE) restoration of the immune tolerance through the manipulation of Tregs can be exploited to treat patients with SLE. New information has revealed that Tregs besides their role in suppressing the immune response are important in tissue protection and regeneration. Expansion of Tregs with low dose IL-2 represents an approach to resolve inflammatory responses and control the autoimmune response. Moreover, control of Treg metabolism can be exploited to restore or improve their function. Here we summarize the function and diversity of Tregs and recent strategies to improve their function in patients with SLE.